Coupling and Cohesion Metrics in Java for Adaptive Reusability Risk Reduction - Iyapparaja, M; Sureshkumar, S (IET Chennai 3rd International Conference on Sustainable Energy and Intelligent Systems (SEISCON 2012), 2012)
Software development has nowadays evolved into a extreme change that uses the best modules being run in various closed and open source software. Extracting the best component and fit them into an ongoing component based development software poses great challenges to run the software error free with desired outcomes. In this proposal we have introduced an `Intelligent Risk Analysis Model (IRAM) for reusability in developing component service oriented software, which are developed using eminent object oriented programming language paradigm Java. This model performs surfing operation into Java object oriented programming modules warehouse, which consists of several availability modules of various projects, and gives a list of suitable module. Those modules are tested on cohesion /coupling testing analysis to determine the individual strength and binding capacity of modules before performing Regression test. Final desirable outcomes are tested on performing regression test while integrating successful level module with domain being developed and proper deployment is made on successful expected outcome of the product. Risk analysis of software project is analyzed for transformation of reusability components risk before transformation Analysis, adaptable risk Analysis, and reusability risk Analysis for package in Java programming. In this paper IRAM model to focus Java package the domain and size of package, integration and dependency relationship of package, measuring the coupling and cohesion in risk metric for development and implementation of reusability package without any risk factor.